Analysis of the impact of information and communication technologies on foreign tourism in the Republic of Croatia - Baldigara, Tea; Penić, Sara (Oeconomica Jadertina, 2020)
In modern business conditions, the development of information and communication technologies has a significant impact on tourism. The Internet is undeniably the most important social phenomenon in the world, which today is a matter of great interest and research. According to statistics on Internet use, the number of Internet users in June 2019 in the world was more than 4 billion users. Assuming that the rise of the Internet as well as the development of other information and communication technologies have significantly changed and influenced modern ways of communication and business in the tourism sector, their better understanding certainly requires a more detailed and systematic qualitative and quantitative analysis. The analysis of tourist demand arising from the use of information and communication technologies, the Internet and social networks, is becoming a key element in forecasting future values, given the increasingly present new trends based on the use of information and communication technologies. The purpose of this paper is to analyse the impact of the number of Internet users in the world on foreign tourism in Croatia, by defining an adequate quantitative model, as a mathematical function that examines the relationship between the number of foreign tourists in the Republic of Croatia and independent variables that reflect the potential impact information and communication technologies have on foreign tourism. Modelling was performed by multiple regression analysis, and the predictive power of the model was evaluated by average absolute percentage and average absolute prognostic error. The results of the research and the conducted tests showed that there is a significant positive relationship between the selected variables and that the designed model is adequate to describe the movement of the selected variables.